Miniplates coated by plasma electrolytic oxidation improve bone healing of simulated femoral fractures on low bone mineral density rats - Momesso, Gustavo Antonio Correa [UNESP] (2021)
The treatment of polytrauma patients represents a great challenge in the maxillofacial and orthopedic surgery fields. Therefore, this study tested the hypothesis that the use of a bioactive coating (by plasma electrolytic oxidation, PEO) on titanium microplates could improve the fracture healing of low bone mineral density (BMD) rats. Thirty female rats underwent bilateral ovariectomy surgery (OVX), and 35 rats underwent fake surgery (SHAM). Three months later, animals were subjected to femoral fracture simulation and were fixed with either non-coated (CONV) or coated (PEO) titanium miniplates. Eight weeks postoperatively, microplate/bone complexes were analyzed through computed microtomography, histometric, confocal microscopy, molecular, and biomechanical analysis. Bioactive elements (Ca and P) were incorporated on the PEO microplate and the surface was modified in a volcano-like structure. In the microCT analysis the OVX/PEO group had greater values for Tb.Th (bone trabecular thickness), Tb.Sp (separation of bone trabeculae) and Tb.N (number of trabeculae) parameters compared to the OVX/CONV group. According to histometric analysis, the OVX/PEO group showed significantly higher new bone formation than the OVX/CONV group (P < 0.05). For the fluorochrome area, the OVX groups (PEO and CONV) showed greater values for calcein precipitation (old bone) than alizarin red (new bone). Molecular results showed greater values for proteins related to the final phase of bone formation (P < 0.05) in the OVX/PEO group. The OVX/PEO group showed higher bone/miniplate system resilience compared to the others (P < 0.05). It was concluded that PEO coating optimizes bone healing on simulated femoral fractures in low bone mineral density rats. This sheds new light in the treatment of osteoporotic patients with bone fractures.